Coronation year : a novel [large type] - Robson, Jennifer, 1970- (Harper Large Print, an imprint of HarperCollinsPublishers, 2023)
Coronation Year, 1953, and a new queen is about to be crowned. The people of London are in a mood to celebrate. Edie Howard, owner and operator of the floundering Blue Lion Hotel, has found the miracle she needs: on Coronation Day, Queen Elizabeth in her gold coach will pass by the hotel's front door, allowing Edie to charge a fortune for rooms and, barring disaster, save her beloved home from financial ruin. Stella Donati, a young Italian photographer and Holocaust survivor, has come to live at the Blue Lion while she takes up a coveted position at Picture Weekly magazine. As she learns the ins and outs of her new profession, Stella discovers a purpose and direction that honor her past and bring hope for her future. James Geddes, a war hero and gifted artist, has struggled to make his mark in a world that disdains his Indian ancestry. At the Blue Lion, even as his friendship with Edie deepens, he begins to suspect that something is badly amiss at his new home. When anonymous threats focus on Coronation Day, Edie and her friends must race to uncover the truth, save their home, and expose those who seek to erase the joy and promise of Coronation Year. -- adapted from back cover